"It Only Reopens Old Wounds": Lived Experiences of Amhara Genocide Survivors From the Miakadra Massacre in Ethiopia. Issue 1 (January 2023) - Bihonegn, Adugna Abebe; Mekonen, Aleminew Abebe
Given the violent conflict and spiraling human rights violations over the last 3 years in Ethiopia, the mass killings and genocide have received little scholarly attention. This phenomenological study investigated the lived experiences of Amhara survivors of the Maikadra massacre, which occurred November 9–10, 2020, in northwestern Ethiopia. In-depth interviews were conducted with 15 survivors who were purposefully selected to understand the meaning and essence of their lived experiences of the massacre. Data were transcribed, translated, and thematically analyzed using a qualitative phenomenological approach. Thematic analysis yielded seven themes centered on premassacre oppression and discrimination, traumatic experiences, emancipation, exacerbating stressors, postmassacre injustice, survivors' primary needs, and coping mechanisms of massacre survivors. The article underscores the role of social workers and community workers in providing professional psychosocial programs and interventions to address massacre survivors' specific needs as individuals, families, and communities.